2011
DOI: 10.1021/ef2004046
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Product Fractions from Hydrothermal Liquefaction of Nannochloropsis sp. and the Influence of Solvents

Abstract: We collected and analyzed the gas, crude bio-oil, dissolved aqueous solids, and insoluble residual solids product fractions arising from hydrothermal liquefaction of Nannochloropsis sp. at 350 °C for 60 min. Most of the carbon and hydrogen in the algal biomass appears in the crude bio-oil product, as desired. A majority of the original nitrogen appears as ammonia in the aqueous phase. We also determined how the solvent used to recover the crude bio-oil affected the yields and compositions of the product fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
155
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(171 citation statements)
references
References 17 publications
15
155
1
Order By: Relevance
“…Many aspects of HTL have been studied including reaction temperature, pressure, retention time, feedstock species, influence of solvents, effects of catalysts, elemental distribution in products, and energy recovery. That work indicates that high temperatures (250°C to 350°C) and high pressures (approximately 10 to 20 MPa) are required and that the HTL oil can contain substantial amounts of nitrogen incorporated from the algal biomass (Alba et al 2012;Biller and Ross 2011;Brown et al 2010;Duan and Savage 2011;Minowa et al 1995;Valdez et al 2011;Vardon et al 2011;Yu et al 2011). From a life cycle perspective considering total energy demand and total emissions, these aspects suggest net energy demand may be higher than for lipid-extracted pathways because heat will be needed to establish the process conditions.…”
Section: Context and Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…Many aspects of HTL have been studied including reaction temperature, pressure, retention time, feedstock species, influence of solvents, effects of catalysts, elemental distribution in products, and energy recovery. That work indicates that high temperatures (250°C to 350°C) and high pressures (approximately 10 to 20 MPa) are required and that the HTL oil can contain substantial amounts of nitrogen incorporated from the algal biomass (Alba et al 2012;Biller and Ross 2011;Brown et al 2010;Duan and Savage 2011;Minowa et al 1995;Valdez et al 2011;Vardon et al 2011;Yu et al 2011). From a life cycle perspective considering total energy demand and total emissions, these aspects suggest net energy demand may be higher than for lipid-extracted pathways because heat will be needed to establish the process conditions.…”
Section: Context and Motivationmentioning
confidence: 99%
“…The HTL yield is defined here to be the mass of HTL oil recovered per dry mass of algae processed, sometimes written as a percentage. Numerous studies are reported in the literature and each reports different yields for the various fractions (Table 1) and different distributions of solids between oil and aqueous phases (Alba et al 2012;Biller and Ross 2011;Brown et al 2010;Duan and Savage 2011;Minowa et al 1995;Valdez et al 2011;Vardon et al 2011;Yu et al 2011). The product distribution may be influenced by many factors, including chemical composition of the algae, reaction temperature, retention time, feedstock solid content, and catalyst usage.…”
Section: Hydrothermal Liquefaction Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst for conventional HTL there is currently no consensus whether the increase in bio-oil yields justifies the additional costs of the solvent extraction procedure [29], it is clear that the HTL of the algae cake in the presence of IPA appears to be only feasible if the water phase is subsequently extracted to recover IPA and the organic reaction products. Consequently, this approach was applied to all subsequent experiments.…”
Section: Optimization Of Product Recovery Methodsmentioning
confidence: 99%
“…Under steady state conditions, biocrude can be recovered from the aqueous phase using organic solvents (53) and subsequently blended with petroleum crude to produce a variety of drop in fuels in conventional refineries (54). Nutrients in the aqueous phase can be recovered to recycle along with CO 2 in the gas phase (55).…”
Section: Introductionmentioning
confidence: 99%